Roof structure - Brown, Stephen; Marshall, Duncan; University of the West of England (Bristol, United Kingdom : University of the West of England, 2001)
This film on roof structure has been completely revised with all new footage, improved graphics and a new voice-over. The first part of the film explains how simple and complex tradisional roofs are constructed. Part two examines the design, fabrication and site construction of trussed raffers, for domestic as well as commercial buildings
Title from title screen
Keywords: Roofing; Roofs -- Design and construction